2017
DOI: 10.1016/j.jpeds.2017.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Early Mortality and Morbidity in Infants with Birth Weight of 500 Grams or Less in Japan

Abstract: Improvements in perinatal-neonatal medicine have improved the survival, but not the rate of major morbidities, of infants with a BW ≤500 g in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 36 publications
2
50
3
Order By: Relevance
“…It is possible some of these differences could be due to differences in attitudes towards resuscitation . Certainly in cohorts where a more liberal approach to resuscitating babies ≤500 g are used, higher survival rates have been reported .…”
Section: Discussionmentioning
confidence: 99%
“…It is possible some of these differences could be due to differences in attitudes towards resuscitation . Certainly in cohorts where a more liberal approach to resuscitating babies ≤500 g are used, higher survival rates have been reported .…”
Section: Discussionmentioning
confidence: 99%
“… However, the use of tcPCO 2 monitoring decreased the frequency of blood gas samplings among ventilated neonates without affecting the duration of mechanical ventilation or clinical outcome . The Neonatal Research Network in Japan, has reported the progress in survival and neurodevelopmental outcome of the infants born at the “limit of viability” . Transcutaneous blood gas monitoring was expected to be useful (30.4%) in future neonatal medical care in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in perinatal–neonatal medicine have greatly improved the survival rate of infants born during the pre‐viable period, or at extremely‐low birthweight . A variety of treatment modalities have been introduced with regard to the concept of minimal handling in neonatal intensive care unit (NICU).…”
mentioning
confidence: 99%
“…The use of such a tool is not always justified, since survival by period is subject to the class of exponential distributions, and in this case it is advisable to use survival analysis regressions, such as the Cox models. The Cox proportional hazards models are used to assess the survival of hypotrophic babies (Inoue, Ochiai and Yasuoka, 2017).…”
Section: Methodsmentioning
confidence: 99%